Effect of Christmas Melon (Laganaria Breviflorus) extract on toxigenic Mycoflora Isolated from Stored Unpolished Rice sold in major Markets in Abeokuta, Nigeria - Amina Badmos; Yetunde Mahmood (Turkish Journal of Agriculture: Food Science and Technology)
Study on toxigenic mycoflora and potential mitigation effect of Christmas Melon (Laganaria Breviflorus) extract in unpolished rice sold in Abeokuta Ogun state of Nigeria was carried out. Unpolished rice gotten from markets in Abeokuta were aseptically transported to the laboratory, serial dilution to reduce the fungal load was carried out and were plated on Potato Dextrose Agar (PDA) and Methyl Red Dessicated Coconut Agar (MRDCA) respectively. Microscopy, macroscopy, toxigenicity test and inhibition studies with the peeled and unpeeled fruit of Laganaria breviflorus fermented for seven days was carried out. Results reveal the predominance of Aspergillus as the major genera, specifically, A. niger, A.flavus, A. parasiticus, A. fumigatus, A. terreus, A. nidulans. Other fungi genera isolated include Penicillium, F`usarium, Mucor, Alternaria and Rhizopus . Of the 11 fungi genera isolated, 9 were toxigenic of which the zones of inhibition of unpeeled whole fruit extract of Laganaria breviflorus range from (3 - 28mm) where A. nidulans shows the highest susceptibility to the whole fruit extract of Laganaria breviflorus while the zone of inhibition of peeled fruit extract of Laganaria breviflorus ranges from (3 - 22mm) where A. parasiticus, Fusarium specie and P.chrysogenum showed the highest susceptibility . As the day progresses the zone of inhibition becomes wider. Unpeeled LB extract exhibited more zones of inhibition than the peeled LB extract. Laganaria breviflorus fruit extracts in the study demonstrates a potential in reducing toxigenic fungi, consequently a means to reducing mycotoxins in staple foods in Nigeria.